Phosphorylation Modulates Catalytic Activity of Mycobacterial Sirtuins - Yadav, Ghanshyam S.; Ravala, Sandeep K.; Malhotra, Neha; Chakraborti, Pradip K. (Frontiers in Microbiology, 2016)
Sirtuins are NAD+-dependent deacetylases involved in the regulation of diverse cellular processes and are conserved throughout phylogeny. Here we report about in vitro transphosphorylation of the only NAD+-dependent deacetylase (mDAC) present in the genome of Mycobacterium tuberculosis by eukaryotic-type Ser/Thr kinases, particularly PknA. The phosphorylated mDAC displayed decreased deacetylase activity compared to its unphosphorylated counterpart. Mass-spectrometric study identified seven phosphosites in mDAC; however, mutational analysis highlighted major contribution of Thr-214 for phosphorylation of the protein. In concordance to this observation, variants of mDAC substituting Thr-214 with either Ala (phospho-ablated) or Glu (phosphomimic) exhibited significantly reduced deacetylase activity suggesting phosphorylation mediated control of enzymatic activity. To assess the role of phosphorylation towards functionality of mDAC, we opted for a sirtuin knock-out strain of Escherichia coli (Δdac), where interference of endogenous mycobacterial kinases could be excluded. The Δdac strain in nutrient deprived acetate medium exhibited compromised growth and complementation with mDAC reversed this phenotype. The phospho-ablated or phosphomimic variant, on the other hand, was unable to restore the functionality of mDAC indicating the role of phosphorylation per se in the process. We further over-expressed mDAC or mDAC-T214A as His-tagged protein in M. smegmatis, where endogenous eukaryotic-type Ser/Thr kinases are present. Anti-phosphothreonine antibody recognized both mDAC and mDAC-T214A proteins in western blotting. However, the extent of phosphorylation as adjudged by scanning the band intensity, was significantly low in the mutant protein (mDAC-T214A) compared to that of the wild-type (mDAC). Furthermore, expression of PknA in the mDAC complemented Δdac strain was able to phosphorylate M. tuberculosis sirtuin. The growth profile of this culture in acetate medium was slow compared to that transformed with only vector. On the other hand, use of a kinase dead variant, PknA-K42N instead of PknA, did not display such behavior, which again supported phosphorylation mediated control of mDAC protein. Thus, our results ostensibly render evidence for cross-talk between two distinct post-translational modifications, phosphorylation and deacetylation, in any bacteria. Bioinformatic analysis further indicated conservation of Thr-214 among different mDAC orthologs, thereby arguing the event as mycobacteria specific.